Biological activity and structure–activity relationship of dehydrodieugenol B analogues against visceral leishmaniasis - Amaral, M; Asiki, H; Sear, CE; Singh, S; Pieper, P; Haugland, MM; Anderson, EA; Tempone, AG (Royal Society of Chemistry, 2023)
Visceral leishmaniasis is a neglected protozoan disease with high mortality. Existing treatments exhibit a number of limitations, resulting in a significant challenge for public health, especially in developing countries in which the disease is endemic. With a limited pipeline of potential drugs in clinical trials, natural products could offer an attractive source of new pharmaceutical prototypes, not least due to their high chemodiversity. In the present work, a study of anti-L. (L.) infantum potential was carried out for a series of 39 synthetic compounds based on the core scaffold of the neolignan dehydrodieugenol B. Of these, 14 compounds exhibited activity against intracellular amastigotes, with 50% inhibitory concentration (IC50) values between 3.0 and 32.7 μM. A structure–activity relationship (SAR) analysis demonstrated a requirement for polar functionalities to improve activity. Lacking mammalian cytotoxicity and presenting the highest potency against the clinically relevant form of the parasite, compound 24 emerged as the most promising, fulfilling the hit criteria for visceral leishmaniasis defined by the Drugs for Neglected Diseases initiative (DNDi). This study emphasizes the potential of dehydrodieugenol B analogues as new candidates for the treatment of visceral leishmaniasis and suggests 24 to be a suitable compound for future optimization, including mechanism of action and pharmacokinetic studies.